Accuracy, unbiasedness, and efficiency of current account growth forecast: Evidence from a large cross section of developed and developing economies - Fazlul Miah; Abdoul Wane (Cogent Economics & Finance, 2018)
We use a previously unexploited consensus survey data set to compare accuracy, unbiasedness and efficiency of Current Account growth forecasts between two panels of 25 developed and 18 developing countries following the methodologies in the existing literature. Forecast errors are bigger for the developing country comparing to the developed country. Developed country forecast errors are unbiased but inefficient. The developing country forecast errors are biased but relatively more efficient. In both the panels, forecast revisions are efficient for the same forecast horizons, but inefficient for the adjacent horizons. Additionally, we find less evidence of forecast smoothing compared to some earlier studies. Forecasters do improve their forecasts as the horizons become shorter although the forecasts fall short of being unbiased and efficient statistically.
Keywords: E27; E37; E00; 330; forecast efficiency; panel estimation; consensus survey; developing economies; rational expectations